2008
DOI: 10.3201/eid1406.071485
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis fromMycobacterium bovisin Binational Communities, United States

Abstract: The epidemiology of tuberculosis (TB) in the United States is changing as the incidence of disease becomes more concentrated in foreign-born persons. Mycobacterium bovis appears to be contributing substantially to the TB incidence in some binational communities with ties to Mexico. We conducted a retrospective analysis of TB case surveillance data from the San Diego, California, region from 1994 through 2005 to estimate incidence trends, identify correlates of M. bovis disease, and evaluate risk factors for de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
93
1
10

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 20 publications
(17 reference statements)
5
93
1
10
Order By: Relevance
“…Spoligotype SB0140 has infected cattle, deer, badgers and people in Source: http://spoltools.emi.unsw.edu.au/ Ireland (de la McLernon et al, 2010), and cattle in the United Kingdom (de la RuaDomenech et al, 2006;McLernon et al, 2010). It has also been reported as the most frequent spoligotype in pigs (Barandiaran et al, 2011), cattle and cats in Argentina (Zumárraga et al, 2009), and humans in the United States (Rodwell et al, 2008) and Mexico (Bobadilla-del Valle et al, 2015). Spoligotype SB0140 has been studied profoundly in the United Kingdom (Smith et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Spoligotype SB0140 has infected cattle, deer, badgers and people in Source: http://spoltools.emi.unsw.edu.au/ Ireland (de la McLernon et al, 2010), and cattle in the United Kingdom (de la RuaDomenech et al, 2006;McLernon et al, 2010). It has also been reported as the most frequent spoligotype in pigs (Barandiaran et al, 2011), cattle and cats in Argentina (Zumárraga et al, 2009), and humans in the United States (Rodwell et al, 2008) and Mexico (Bobadilla-del Valle et al, 2015). Spoligotype SB0140 has been studied profoundly in the United Kingdom (Smith et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, we have recently shown that living M. tuberculosis organisms can be detected in the stools of patients with pulmonary tuberculosis (El Khechine et al, 2009). M. bovis, however, is also efficiently transmitted directly by the aerosol route, being responsible for outbreaks of tuberculosis (Rodwell et al, 2008) and bovine tuberculosis (Wilkins et al, 2008). It has also been demonstrated that M. bovis can survive ingestion by amoebae, which suggests that protozoa could significantly enhance the survival of M. bovis in the soil and hence may be instrumental in the transmission of bovine tuberculosis (Taylor et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report on the incidence of M. bovis in San Diego, CA, highlighted the importance of routine species-level identification in U.S. tuberculosis (TB) surveillance. That investigation reported the growing incidence of TB caused by M. bovis (45% of all culture-positive TB cases in children between 1994 and 2005), which may be representative of other communities in the United States (17). In New York, 3 to 7% of the MTBC specimens that our laboratory receives each year are identified as species other than M. tuberculosis.…”
mentioning
confidence: 99%